Evaluation of online learning in Natural Science for junior high school - Nurrana Fitria Luthfi; Syukrul Hamdi (Jurnal Penelitian dan Evaluasi Pendidikan, 2020)
This research aims to evaluate the online learning system in natural science subject for the junior high school level in Yogyakarta. This research uses CIPP (Context, Input, Process, Product). The research subjects are two school principals, five natural science teachers, and 267 grade VII, VIII, and IX students in State Junior High School (sekolah menengah pertama negeri or SMPN) 9 Yogyakarta and Nurul Ummah Islamic Junior High School (Madrasah Tsanawiyah or MTs), Kotagede, Yogyakarta. Data were collected through questionnaires and interview guidelines validated through the process of expert judgment to prove the construct validity using Exploratory Factor Analysis (EFA). The instrument's reliability was analyzed using Alpha Cronbach, while the results were analyzed using the qualitative descriptive method. According to the context aspect, the results of this research are in the form of online school program objectives to meet the needs of flexibility, ideal operational technology tools, and the professionalism of Natural Science teachers in practicum activities considered in the fairly good category. According to the input context, the results are in the form of an online system supported by the internet access facility and the scheduling, procedure, and capabilities of Natural Science teachers, considered in the good category. According to the process aspect, the results are in the form of online learning, considered in the good category. Meanwhile, according to the product aspect, the results are in the form of quality achievement on learning outcomes and the support of the online learning system implementation, considered in the good category.